2009
DOI: 10.1111/j.1872-034x.2008.00444.x
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous transretroperitoneal direct approach to occlude a major shunt in a patient with extrahepatic portal–systemic encephalopathy

Abstract: A 73-year-old woman had sudden dystrophy and amnesia in our hospital. Her serum ammonia level was high. Marked collateral vessels from the splenic vein to the left renal vein around the spleen were seen on a computed tomography (CT) scan with contrast enhancement. An abdominal angiogram showed that the direction of the splenic vein was hepatofugal on superior mesenteric arterial portography, with a marked splenorenal shunt on splenic arterial portography. Hepatic encephalopathy due to a marked extrahepatic por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…It was suggested that UVR directs blood entering the systemic circulation without liver detoxification, which may increase HE risks [23] . Based on the phenomenon that collateral circulation increases the incidence of HE, clogging of collateral vessel recanalization may be used to treat HE, and the ascites and esophageal varices do not significantly aggravate the HE incidence [24] . When HE was clinically found, an abdominal CT scan was done to detect whether it was combined with portal vein collateral branch, which was important for developing a reasonable therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that UVR directs blood entering the systemic circulation without liver detoxification, which may increase HE risks [23] . Based on the phenomenon that collateral circulation increases the incidence of HE, clogging of collateral vessel recanalization may be used to treat HE, and the ascites and esophageal varices do not significantly aggravate the HE incidence [24] . When HE was clinically found, an abdominal CT scan was done to detect whether it was combined with portal vein collateral branch, which was important for developing a reasonable therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%